Boundary between statutory auditing and consulting services, case of information technology services: comparative law - IDRISSI KAITOUNI , Ahmed; AOUAME , Abdelouahab (Revue Internationale des Sciences de Gestion, 2025)
The statutory auditor is entrusted with a mission of general interest, its primary goal is to certify the annual accounts of compagnies by verifying the fairness and regularity of the accounts and financial statements, while adhering to the principles of independence and non-interference in management decisions, which are widely accepted both nationally and internationally. However, while performing its main mission, the statutory auditor may, in various situations, become dependent on the audited company, particularly in terms of appointment, remuneration and access to information. This dependence may intensify when providing non audit services. This situation highlights the need to strengthen the legal framework and safeguard mechanisms to ensure the auditor’s independence and uphold the credibility of the audit mission. Thus, this article aims to analyze the approaches adopted by different regulators to regulate and protect auditor independence when providing non-audit-services to audit clients, especially in the field of information technology.